2009
DOI: 10.1145/1462055.1462056
|View full text |Cite
|
Sign up to set email alerts
|

A unified information-theoretic framework for viewpoint selection and mesh saliency

Abstract: Viewpoint selection is an emerging area in computer graphics with applications in fields such as scene exploration, image-based modeling, and volume visualization. In particular, best view selection algorithms are used to obtain the minimum number of views (or images) in order to understand or model an object or scene better. In this article, we present a unified framework for viewpoint selection and mesh saliency based on the definition of an information channel between a set of viewpoints (input) and the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
127
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 29 publications
1
127
0
Order By: Relevance
“…In [26], it has been shown that one of the main properties of VMI is its robustness to deal with any type of discretisation or resolution of the volume data set. The same behavior can be observed for polygonal data [6]. From the viewpoint information channel, the viewpoint entropy (VE) of viewpoint v is defined by…”
Section: Viewpoint Information Channelmentioning
confidence: 55%
See 3 more Smart Citations
“…In [26], it has been shown that one of the main properties of VMI is its robustness to deal with any type of discretisation or resolution of the volume data set. The same behavior can be observed for polygonal data [6]. From the viewpoint information channel, the viewpoint entropy (VE) of viewpoint v is defined by…”
Section: Viewpoint Information Channelmentioning
confidence: 55%
“…Viola et al [26] proposed a viewpoint information channel and used the viewpoint mutual information to automatically determine the most expressive view on a selected focus. A unified information-theoretic framework for viewpoint selection, ambient occlusion, and mesh saliency for polygonal models has been presented in [6,7]. Next we review the definitions of viewpoint information channel, viewpoint mutual information, and viewpoint entropy in volume visualization.…”
Section: Viewpoint Information Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…It can improve 3D model examination by evaluating view-points through Jensen-Shannon divergence [7] to reveal important model features. It can also identify and emphasise important parts of a volumetric model [18], or can modify the normal vector of each mesh vertex according to the variation in its luminance in order to enhance the visual appearance of important mesh features [30].…”
Section: Visual Saliencymentioning
confidence: 99%